Hubungan Unsur Iklim terhadap Produksi Tanaman Cabai Rawit (Capsicum frutescens L.) di Kabupaten Nganjuk - Nurcahyo, Agung Wilis; Junaidi; Hadiyanti, Nugraheni; Nareswari, Aptika Hana Prastiwi (Universitas Kadiri, 2024)
Patianrowo District, Nganjuk Regency, located at an altitude of 45 m above sea level, is an essential area for producing cayenne pepper plants. Rainfall is considered to be crucial in the growth of cayenne pepper plants in Patianrowo. This association may be due to sufficient rainfall, providing necessary soil moisture and supporting photosynthesis processes. Meanwhile, air temperature and humidity also affect cayenne pepper production. These plants develop optimally at certain temperatures and humidity; extreme changes can inhibit plant growth and yield. This research aims to analyze the relationship between climate elements on the production of cayenne pepper plants. The research was carried out by applying descriptive-analytical research methods. Secondary data collected includes cayenne pepper production data for 2012-2021 and climate element data (temperature, solar radiation, air humidity and rainfall) in 2012-2021. The data obtained was analyzed using correlation and regression tests. Data from the analysis showed a relationship between climate elements and cayenne pepper production in Patianrowo District, Nganjuk Regency. Solar radiation has a significant effect on cayenne pepper production by 55.84%, temperature has an effect of 48.83%, and air humidity has an effect of 46.36%. The production estimation model for cayenne pepper based on solar radiation is Y= 26,461X –181,459, the production estimation model based on temperature is Y = 94,250X – 2,234,167, and the estimation model based on humidity is Y = 407,659 – 4,643X. Kecamatan Patianrowo, Kabupaten Nganjuk terletak pada ketinggian 45 m dpl merupakan wilayah penting dalam produksi tanaman cabai rawit. Curah hujan diduga memainkan peran krusial dalam pertumbuhan tanaman cabai rawit di Patianrowo. Keterkaitan ini mungkin disebabkan oleh curah hujan yang mencukupi, memberikan kelembaban tanah yang diperlukan dan mendukung proses fotosintesis. Sementara itu, suhu udara dan kelembaban udara juga mempengaruhi produksi cabai rawit. Tanaman ini cenderung berkembang optimal pada suhu dan kelembaban tertentu, dan perubahan ekstrim dalam kondisi ini dapat menghambat pertumbuhandan hasil tanaman. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara unsurunsur iklim terhadap produksi tanaman cabai rawit. Penelitian dilaksanakan dengan menerapkan metode penelitian deskriptif analitik. Data sekunder yang dikumpulkan meliputi data produksi cabai rawit periode 2012-2021 dan data unsur iklim (suhu, radiasi matahari, kelembaban udara dan curah hujan) pada tahun 2012-2021. Data yang diperoleh dianalisis mengguunakan uji korelasi dan regresi. Data hasil analisis menunjukkan adanya hubungan antara unsur iklim terhadap produksi cabai rawit di Kecamatan Patianrowo, Kabupaten Nganjuk. Radiasi matahari berpengaruh nyata terhadap produksi cabai rawit sebesar 55,84%, suhu berpengaruh sebesar 48,83% dan kelembaban udara berpengaruh sebesar 46,36%. Model pendugaan produksi cabai rawit berdasarkan radiasi maatahari adalah Y= 26.461X – 181.459, model pendugaan produksi berdasarkan suhu adalah Y = 94.250X – 2.234.167 dan model pendugaan berdasarkan kelembaban adalah Y = 407.659 – 4.643X.